Legal and Economic Aspects of Landmark Preservation - Case of the Czech Republic - Janderová, Jana; Tůmová, Dominika (STEF92 Technology Ltd., 2019)
Landmark preservation is an endeavor to conserve cultural heritage objects for future generations. Necessarily, to protect cultural objects from peril the states impose restrictions on individual owners, namely regarding the way these are to be maintained and repaired. Such constraints are in public interest. However, public interest might be contradicting the individual interests of the owners, or at least it might bring extra costs to them. The contribution seeks to explain what legal provisions restrict owners of historical objects and how these restrictions may be economically compensated in the Czech Republic. The paper focuses mainly on repair subsidies that may be granted by cities to the owners. Relevant statutory laws and case law of administrative courts are analyzed. To demonstrate the theoretical findings, practice of two regional cities subsidies programs is compared. In conclusion, the findings are summarized and recommendations provided.
Právní a ekonomické aspekty ochrany památek - případ České republiky
Keywords: landmark preservation; subsidies; public interest; restrictions; grants; ochrana památek; podpora; veřejný zájem; omezení; granty